Eksistensi Peran Perempuan di Masa Pandemi COVID-19: Studi Kasus 3 Perempuan di Yogyakarta: The Existence of Women's Roles during the COVID-19 Pandemic: A Case Study of 3 Women in Yogyakarta - Napsiah Napsiah; Ahmad Norma Permata; Dwi Nur Laela Fithriya; Hikmalisa Hikmalisa (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
The COVID-19 pandemic has erased the stereotype of the domestication of women with the status of women as housewives and career women, which has an impact on women’s double burden, namely doing domestic work and public work. This article aims to prove that the domestic sector has strengthened the existence of women. This research is descriptive qualitative by interviewing three career women in Yogyakarta. They were selected by direct pointing because these women can provide relevant information in this study. Indirect observations were carried out to explore information that was not conveyed at the time of the interview. Information from journals, websites, and newspapers was used to strengthen the data. The results showed that women’s ability to manage the household had an effect during the COVID-19 pandemic, namely the Work From Home (WFH) policy. Women’s domestic roles include women’s managerial abilities in utilizing home facilities such as the living room, family room, workspace, and even the kitchen room and mastery of home facilities such as Wi-Fi, laptops, and cellphones used by other family members. It also provides ample opportunity for women to demonstrate their ability to carry out domestic sector jobs such as cooking, protecting family members, and doing public work such as seminars, teaching, selling services, business, and forming social groups to help disaster victims. In line with that, the role of women in the domestic sector and public sector is balanced, thereby strengthening women’s existence during the COVID-19 pandemic.